2011
DOI: 10.1007/s12029-010-9245-x
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab 5 or 7.5 mg/kg in Metastatic Colorectal Cancer Can Be Infused Safely Over 10 Minutes

Abstract: Bevacizumab 5 or 7.5 mg/kg in MCRC can be infused safely over 10 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…They saw only two grade 2 infusion reactions in the 10-min group (a total of 527 doses given). Since these symptoms were easily treated and comparable to numbers they found in literature, the authors concluded that bevacizumab could be safely infused in 10 min in this group of patients (14). Shah et al stated that besides no hypersensitive reactions, there was also no increase in proteinuria and hypertension seen when a 0.5 mg/kg/min bevacizumab infusion was given (15).…”
Section: Resultssupporting
confidence: 75%
“…They saw only two grade 2 infusion reactions in the 10-min group (a total of 527 doses given). Since these symptoms were easily treated and comparable to numbers they found in literature, the authors concluded that bevacizumab could be safely infused in 10 min in this group of patients (14). Shah et al stated that besides no hypersensitive reactions, there was also no increase in proteinuria and hypertension seen when a 0.5 mg/kg/min bevacizumab infusion was given (15).…”
Section: Resultssupporting
confidence: 75%
“…The present retrospective study in NSCLC patients confirms the results of Dohn et al and Mahfoud et al [6,7] in colorectal cancer patients regarding the feasibility of bevacizumab 7.5 mg/kg over 10 min. No increase of toxicity was observed when switching from the standard 90-, 60-and 30-min sequence to an infusion duration of 10 min from the initial administration of bevacizumab 7.5 mg/kg/week.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, a subset of patients received bevacizumab at a dose of 7.5 mg/kg (every 3 weeks, in combination with capecitabine and oxaliplatin), for an infusion rate of 0.75 mg/kg/min (higher than that reported in phase 1 studies). More recently, Mahfoud et al [7] also described a cohort of colorectal cancer patients receiving 192 doses of bevacizumab 7.5 mg/kg over 10 min, with a favourable immediate toxicity profile.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of retrospective studies of various therapeutic antibodies (bevacizumab, rituximab, daratumumab, and infliximab), as well as prospective studies (ramucirumab and nivolumab) that implemented shortened infusion times and included IRR incidence as an end point was presented (Table S2). [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] Reportedly, a shorter infusion time did not appear to increase the incidence of IRRs in these studies. Thus, the evidence developed using MIDD approaches indicated that the commonly held perception that infusion rate is related to IRR incidence may not hold true for the antibodies studied.…”
Section: Results and Impactmentioning
confidence: 99%
“…Lilly then conducted a literature review for supportive evidence, as suggested by the FDA. A summary of retrospective studies of various therapeutic antibodies (bevacizumab, rituximab, daratumumab, and infliximab), as well as prospective studies (ramucirumab and nivolumab) that implemented shortened infusion times and included IRR incidence as an end point was presented ( Table ) 52–66 . Reportedly, a shorter infusion time did not appear to increase the incidence of IRRs in these studies.…”
Section: Rationale and Implementation Of Midd To Inform The Developme...mentioning
confidence: 99%